PENGARUH MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DI KELAS VI SD NEGERI 097378 SIBOPO - Romaida Karo Karo (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
This study aims to determine the effect of science learning outcomes on sixth grade students of SD N 097378 Sibopo with the Think Pair Share (TPS) learning model. This research is an experimental research using one group pretest positives design. The research sample was 22 grade VI students of SD N 097378 Sibopo. The technique of collecting data on student learning outcomes uses test techniques with instruments in the form of multiple choice tests with one correct answer. As a follow-up, the collected data was analyzed using the one sample t-test (t-test) to test the effect of student learning outcomes. ipa class VI at SD N No. 097378 Sibopo with tcount 22.51 > ttable 1.72 and is supported by the difference in the average score obtained by students from the post-test score of 76.36 and the pre-test score of 63.00.